A comparison of two treatment protocols in the management of exercise-associated postural hypotension (EAPH) : a randomised clinical trial - Anley, Cameron (MRC/UCT RU for Exercise and Sport Medicine, 2014)
Includes bibliographical references (p. 79-83).